2019
DOI: 10.1007/s11906-019-0930-2
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Endothelial Dysfunction in Patients with Obesity

Abstract: Purpose of Review To examine the state of the art on the pathogenesis of endothelial dysfunction in the microcirculation of patients with obesity, focusing on the complex relationship between the consolidated and the novel mechanisms involved in this alteration.Recent Findings Human obesity is associated with vascular endothelial dysfunction, caused by a reduced nitric oxide availability secondary to an enhanced oxidative stress production. Pro-inflammatory cytokine generation, secreted by perivascular adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 42 publications
0
43
0
5
Order By: Relevance
“…Also, males tend to accumulate fat at the visceral depot at any age ( Matsuzawa et al, 1995 ) which causes males to have more VAT than females. Moreover, as previously discussed, VAT, as an endocrine organ ( Wajchenberg, 2000 ), had more negative effects than SAT, which may lead to vascular endothelial damage ( Virdis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, males tend to accumulate fat at the visceral depot at any age ( Matsuzawa et al, 1995 ) which causes males to have more VAT than females. Moreover, as previously discussed, VAT, as an endocrine organ ( Wajchenberg, 2000 ), had more negative effects than SAT, which may lead to vascular endothelial damage ( Virdis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, animal studies provide some insight on the potential impact of obesity on the occurrence of CSVD. For example, a previous study ( Virdis et al, 2019 ) suggested that the pathology of endothelial dysfunction caused by obesity might be related to oxidative stress, inflammation, or enzyme-mediated pathways and may later manifest as CSVD. Interestingly, visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) have different effects on disease formation ( Gil et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in both experimental animals and humans have identified the loss of NO as a central feature associated with the development of HFD‐ and obesity‐induced vascular dysfunction (Damjanovic & Barton, ; Engin, ; Virdis et al, ). There are also established sex differences in the NO/NOS pathway, making this an attractive potential mechanism to explain sex differences in vascular function.…”
Section: Endothelial Dysfunction In Cvdmentioning
confidence: 99%
“…The function and structure of these vasculatures are different: The macrovasculature buffers the increases in blood flow pulsatility, preventing tissue injury, and distributes blood to the body, whereas the microvasculature regulates vascular tone/resistance and blood pressure. In adults with obesity, endothelium-dependent vasodilation in both macro- and micro-vasculature are impaired [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%